Complications in CO2 Laser Transoral Microsurgery for Larynx Carcinomas - Chiesa Estomba, Carlos Miguel; Reinoso, Frank Alberto Betances; Velasquez, Alejandra Osorio; Fernandez, Jose Luis Rodriguez; Conde, Jose Luis Fariña; Hidalgo, Carmelo Santidrian (International Archives of Otorhinolaryngology, 2016)
Introduction Transoral laser microsurgery (TLM) has established itself as an effective option in the management of malignant tumors of the glottis, supraglottis, and hypopharynx. Nonetheless, TLM is not a harmless technique. Complications such as bleeding, dyspnea, or ignition of the air may appear in this type of surgery.Objective The aim of this study is to describe the complications that occurred in a group of patients treated for glottic and supraglottic carcinomas in all stages by TLM.Methods This study is a retrospective analysis of patients diagnosed with squamous cell carcinoma of the glottis and supraglottis for all stages (T1, T2, T3, T4), N -/ + , M -/+ treated with TLM between January 2009 and March 2012 in a tertiary hospital.Results Ninety-eight patients met the inclusion criteria, which had undergone a total of 131 interventions. Ninety-four (95.9%) patients were male and 4 (4.1%) were female. The mean age was 64.2 years (± 10.7 years = min 45; max 88). The presence of intraoperative complications was low, affecting only 2% of patients. Immediate postoperative complications occurred in 6.1%, whereas delayed complications affected 13.2% of patients, without any of them being fatal.Conclusion TLM has shown good oncologic results and low complication rate compared with traditional open surgery during intervention, in the immediate and delayed postoperative period and in the long-term with respect to radiotherapy.
Keywords: complications; CO2 laser; larynx; carcinoma